2014
DOI: 10.1089/end.2014.0342
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Clinical Trial of Vesicare (Solifenacin) in the Treatment of Urinary Incontinence After Radical Prostatectomy

Abstract: Solifenacin is well tolerated in post radical prostatectomy patients with a 15% withdrawal rate due to side effects. These results formed the basis of a large, prospectively randomized clinical trial comparing the effects of solifenacin versus placebo in a population of men incontinent after RARP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“… 3 , 4 In addition, if after the first week postcatheter removal, a patient is utilizing two or more “wet” urinary pads, an anticholinergic medication for 2 to 3 months is recommended to reduce the time to pad-free status. 5 …”
Section: Postoperative Carementioning
confidence: 99%
“… 3 , 4 In addition, if after the first week postcatheter removal, a patient is utilizing two or more “wet” urinary pads, an anticholinergic medication for 2 to 3 months is recommended to reduce the time to pad-free status. 5 …”
Section: Postoperative Carementioning
confidence: 99%
“… 28 Solifenacin has been widely applied clinically and there are several published studies about the therapeutic effects of solifenacin after radical prostatectomy, but there are some differences in the results for urinary incontinence. 9 11 …”
Section: Discussionmentioning
confidence: 99%
“… 7 Solifenacin, a once-daily competitive muscarinic receptor antagonist has been found to improve DO symptoms, including incontinence, urgency, and frequency, with a low incidence of treatment-limiting adverse events. 8 Solifenacin has been used in several trials post-radical prostatectomy, 9 11 but there is a lack of research for the application of solifenacin in cases of LRP. The main difference in this current study is that all of the patients had undergone laparoscopic procedures, rather than robotic or open procedures, for which there are few data.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies reported patients were still incontinent 1 to 3 weeks after catheter removal, have the highest risk of prolonged incontinence and are most likely to benefit from pharmacotherapy. 14,16 Use of antimuscarinic agents after radical prostatectomy is also supported from urodynamic investigations. Initial reports focused on UDS findings in patients with urinary incontinence after radical prostatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…11e13 A phase I trial evaluating solifenacin in the post-RARP setting demonstrated that 1) there were no significant safety issues with solifenacin after RARP and 2) the prediction of severely delayed return of continence could not be established by standard baseline preoperative assessment (AUASS, prostate weight etc). 14 Significant research has revealed that the degree of leakage in the first few days after catheter removal after RP may be the best predictor of prolonged incontinence, 15e17 as 95% become pad-free by 90 days if they only required zero or 1 pad 4 to 7 days after catheter removal. 16 For patients with post-prostatectomy incontinence with mixed urinary incontinence symptoms and/or those with an urgency component, EAU (European Association of Urology) guidelines recommend a trial of antimuscarinics.…”
mentioning
confidence: 99%